Changes in ventral prefrontal-subcortical network connectivity during the course of remission from bipolar mania - Jennifer E. Siegel-Ramsay; Elizabeth Lippard; Thomas Blom; Wade Webber; Cal Adler; David E. Fleck; Melissa P. DelBello; Jorge R.C. Almeida; Stephen M. Strakowski (Journal of Mood and Anxiety Disorders)
Background: Dysregulated ventral prefrontal-subcortical networks are implicated in bipolar disorder, although how connectivity changes within these networks during the emergence and resolution of affective episodes is unclear. To address this knowledge gap, in this post-hoc study, we investigated longitudinal changes in prefrontal-subcortical connectivity during remission from mania in individuals with bipolar I disorder. Methods: We followed 35 individuals with bipolar I disorder through eight weeks of treatment for a manic episode. Using mixed models, we compared changes in ventral prefrontal-subcortical connectivity between individuals who remitted (n = 16, Young Mania Rating Scale/Hamilton Depression Rating Scale < 10 by week eight) and those who did not (n = 19) during emotional distractor conditions of the continuous performance task (CPT-END), a cognitive attentional task with emotional and neutral distractors; at baseline, one and eight weeks of treatment covarying for age and sex. Results: During the eight-week trial, significant group-by-time interactions were found between medial prefrontal cortex and right inferior frontal gyrus pars triangularis. There was also a group-by-time interaction in connectivity between prefrontal cortex and left thalamus, bilateral amygdala, and pregenual anterior cingulate cortex. Conclusion: These results highlight distinct ventral prefrontal-subcortical connectivity patterns characterizing the remitted state in bipolar disorder during tasks requiring focused attention amid emotional distractions. In the context of previous research, remission was associated with more normative connectivity between medial prefrontal and both thalamus and ventrolateral prefrontal cortex. However, while ventral prefrontal–paralimbic/limbic connectivity may show improvement with symptom remission, it may not fully normalize, suggesting residual functional abnormalities despite clinical recovery.